2016
DOI: 10.1186/s12915-016-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

The topology, structure and PE interaction of LITAF underpin a Charcot-Marie-Tooth disease type 1C

Abstract: BackgroundMutations in Lipopolysaccharide-induced tumour necrosis factor-α factor (LITAF) cause the autosomal dominant inherited peripheral neuropathy, Charcot-Marie-Tooth disease type 1C (CMT1C). LITAF encodes a 17 kDa protein containing an N-terminal proline-rich region followed by an evolutionarily-conserved C-terminal ‘LITAF domain’, which contains all reported CMT1C-associated pathogenic mutations.ResultsHere, we report the first structural characterisation of LITAF using biochemical, cell biological, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…In this study, we demonstrated that SIMPLE binds specifically to PI4P through the 115–141 region within the SLD, and that this binding was cysteine-independent. Recently, two groups independently revealed that SIMPLE is a monotopic zinc-binding protein, and that the function of cysteine residues outside the 114–139 hydrophobic helical region is to mediate zinc binding for stabilization of the protein structure [ 12 , 13 ]. On the other hand, the FYVE domain, which binds PI3P in a cysteine-dependent manner, requires two zinc ions for proper structure [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we demonstrated that SIMPLE binds specifically to PI4P through the 115–141 region within the SLD, and that this binding was cysteine-independent. Recently, two groups independently revealed that SIMPLE is a monotopic zinc-binding protein, and that the function of cysteine residues outside the 114–139 hydrophobic helical region is to mediate zinc binding for stabilization of the protein structure [ 12 , 13 ]. On the other hand, the FYVE domain, which binds PI3P in a cysteine-dependent manner, requires two zinc ions for proper structure [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al . also reported that the 114–139 hydrophobic helical region interacts with phosphatidylethanolamine (PE) [ 12 ]. Using liposome sedimentation assays, we tested the ability of SIMPLE to bind PI4P.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,16 Indeed, recent studies have shown that LITAF has a cysteine-rich region that coordinates zinc. 17,18 We explored whether LITAF could positively regulate the transcription of myelin genes. To this aim, HEK293 cells were cotransected with phPMP22enh-Luciferase and the plasmids encoding for the human LITAF sequence.…”
Section: Egr2 P397h Has a Decreased Transcriptional Activitymentioning
confidence: 99%